Integrating Circle-Seq with transcriptomics reveals genome-wide characterization of extrachromosomal circular DNA for dilated cardiomyopathy - Lin, Zhenhao; Dai, Fangjie; Li, Bo; Zhao, Yongchao; Wang, Changqian (Biology direct, 2024)
Extrachromosomal circular DNAs (eccDNAs) are commonly found in various tumors and play a critical role in promoting oncogenesis. However, little is known about the characteristics and nature of eccDNAs in human heart failure. The aim of this study was to comprehensively analyze eccDNAs in human heart failure caused by dilated cardiomyopathy (DCM) and explore their potential functions. Circle-Seq and RNA-Seq were performed in cardiac tissue samples obtained from patients with DCM and healthy controls to identify eccDNAs and corresponding genes. Inward PCR, outward PCR and Sanger sequencing were conducted to validate the circular structure of eccDNAs. Bioinformatics was employed to probe the transcriptional activity of eccDNAs and their potential roles in the development of DCM. Ligase assisted minicircle accumulation strategy was used to synthesize a 500 bp circular DNA with a random sequence. EccDNAs originated from all chromosomes, with the majority being less than 1 kb in size and about half containing genes or gene fragments. They were derived from specific repeat elements and primarily mapped to 5'UTR, 3'UTR, and CpG islands. Gene-rich chromosomes 17 and 19 exhibited higher eccDNA enrichment. Sequence motifs flanking eccDNA junction sites displayed frequent nucleotide repeats. The circular structure of eccDNAs were confirmed. Integration of Circle-Seq and RNA-Seq data identified that large eccDNAs can be directly transcribed in non-dividing cardiomyocytes, indicating their potential roles in gene expression. Small circular DNA elicited a stronger cytokine response than linear DNA with the same sequence. Our work provided a detailed profiling of eccDNAs in both healthy and DCM hearts and demonstrated the potential functions of both large and small eccDNAs. These findings enhance the comprehension of the role of eccDNAs in cardiac pathophysiology and establish a theoretical foundation for future investigations on eccDNAs in DCM.